Experimental and numerical analysis of a novel Darrieus rotor with variable pitch mechanism at low TSR - Zouzou, B.; Dobrev, I.; Massouh, F.; Dizene, R. (Energy (Oxford), 2019)
The Darrieus vertical axis wind-turbine (VAWT) has been the subject of numerous recent studies aimed at improving its aerodynamic performance in order to locate it in urban areas. This article is devoted to the study of an original VAWT with variable-pitch and low tip speed ratio TSR which is favorable to noise reduction and can operate at low velocity wind. The aerodynamic performance of this turbine is studied experimentally in wind tunnel as well as by CFD. In order to obtain the 3D-flow field around the wind turbine rotor, the numerical simulations are performed by means of detached eddy simulation method (DES). The simulation of pitch variation is made possible by using sliding-mesh method. Thus a specially created program adapts the pitch depending on the blade azimuthal position during rotation. The obtained results show that adapted pitch blades are preferable because they permit to obtain a power coefficient Cp that rivals other VAWT in the case of TSR<1. The maximum torque fluctuation during rotation is lower in the case of adapted variable-pitch compared to fixed-pitch and thus the maximum aerodynamic loads on the structure can be reduced. Moreover, the pitch adaptation leads to lower interaction effects between the upstream-blade wake and down-stream blades.